In silico discovery of novel inhibitors from Northern African natural products database against main protease (Mpro) of SARS-CoV-2. Issue 7 (3rd May 2023) - Byadi, Said; Oblak, Domen; Kassmi, Yassine; Sadik, Karima; Hachim, Mouhi Eddine; Podlipnik, Črtomir; Aboulmouhajir, Aziz
Abstract: The recent outbreak of COVID-19 (Coronavirus Disease 2019), caused by a novel SARS-CoV-2 virus, has led to public health emergencies worldwide where time is as important as equipment to save lives. Antimalarial drugs such as hydroxychloroquine and chloroquine derivatives are used in emergencies but they are not suitable for patients with high blood pressure, diabetes and heart problems. Since there are no approved drugs for this disease, science is challenged to find vaccines and new drugs. Therefore, as part of our Silico drug design strategy, we identified drug-like compounds that inhibit replication of the main protease (Mpro) of SARS-CoV-2 based on receptor-based virtual database screening, molecular docking, molecular dynamics, and drug-similarity profiling from the NANPDB natural products database available at North African. The two resulting hit compounds named 5- Chloro-Omega-hydroxy-1-O-methylemodin and cystodion E showed the highest binding energy with Mpro of SARS-CoV-2 and strong inhibitory activity compared with the previously published N3 inhibitor. The complexes of these two compounds were validated by molecular dynamics analysis (RMSD, RMSF, Rg, total number of hydrogen bonds and secondary structure fractions of the protein in the complex) as the best method to evaluate the biological stability of the system. Therefore, these molecules deserve more attention in drug development compared to COVID-19. Highlights: A large database of natural compounds was screened against nCoV-2's Mpro. Molecular docking and Molecular dynamics were used as powerful methods. Two compounds were found are very attractive to inhibit Mpro of nCoV-2. ADME-Tox profiling is evaluated the active compounds are not cancerogenic. Communicated by Ramaswamy H. Sarma